Interactive Storytelling Books for Fostering Inclusion of Children with Special Needs - Jadán-Guerrero, Janio (2020)
Children with Special Needs may have difficulty understanding the content of a book or associating words and sentences with their meaning. Teachers use the storytelling as a powerful literacy tool which engage children in making connections between academic content and pedagogy. This strategy is also useful to integrate the diversity of the classroom. Increasing or varying the types of materials available to children is another way to make the classroom more inclusive. This paper proposes a new approach for fostering interaction and inclusion development during shared reading. We sought to increase the interactivity of traditional tale books by incorporating elements of technology and storytelling. To develop prototypes we recruited 30 teachers divided into six groups. Each group worked with two challenges: (1) to incorporate technology into a traditional storybook and (2) create an interactive storytelling book for left-handed children. During five work sessions each group developed two proposals: The first proposal was designed with QR codes and the second with NFC tags and augmented reality patterns to facilitate left-handed activities among teachers and children. The proposals were evaluated in the classroom and with experts’ reviews, finding interesting results. © 2020, The Editor(s) (if applicable) and The Author(s), under exclusive license to Springer Nature Switzerland AG.